2018
DOI: 10.1016/j.esd.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Does energy efficiency matter to real estate-consumers? Survey evidence on willingness to pay from a cost-optimal analysis in the context of a developing country

Abstract: In most countries, energy efficiency at the residential level has been largely delegated to the dynamics of realestate markets after setting a minimum level. This regulatory definition is in certain cases supplemented by energy performance certificates, such as in the case of the European Union. This approach is based on the understanding that avoided energy-consumption costs positively affect the willingness to pay for them, thus leading to higher prices capable of offsetting production costs and thereby enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…The result indicated that the barrier lying in the core position of new residential building energy efficiency promotion in China is "the ineffectiveness in translating expected energy savings into profits/benefits for home-buyers". This was also noted as the "energy efficiency gap" or "energy efficiency paradox" in other literature [39,55,56]. It broadly refers to the slower actual diffusion of energy-efficient goods (buildings, technologies and relevant energy-efficient products in new residential building sector) than the socially optimal level [57,58].…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…The result indicated that the barrier lying in the core position of new residential building energy efficiency promotion in China is "the ineffectiveness in translating expected energy savings into profits/benefits for home-buyers". This was also noted as the "energy efficiency gap" or "energy efficiency paradox" in other literature [39,55,56]. It broadly refers to the slower actual diffusion of energy-efficient goods (buildings, technologies and relevant energy-efficient products in new residential building sector) than the socially optimal level [57,58].…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…On the other hand, less educated households appear to be more influenced by their attitudes toward EEMs and perceived behavioural control [32]. Encinas et al [39] found that in Santiago, Chile income and educational level, as well as other demographic aspects, have a positive influence on WTP. In the Latin American country, households with young children and respondents with higher education seem to have a more environmentally friendly behaviour [39].…”
Section: Perception and Attitudesmentioning
confidence: 99%
“…Although many studies have focused on building energy performance and related policies, only a few studies have attempted to analyze consumer perceptions of energy-efficient buildings [20,21,[39][40][41][42][43]. Hoffman and Henn (2008) [39] and Yau (2012) [40] demonstrate that consumers are affected by several factors when deciding to move into energy-efficient buildings, such as economic or/and psychological reasons.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hoffman and Henn (2008) [39] and Yau (2012) [40] demonstrate that consumers are affected by several factors when deciding to move into energy-efficient buildings, such as economic or/and psychological reasons. Encinas et al (2018) [42] and Liu et al (2018) [43] investigate the consumers' willingness to pay for energy efficient buildings, and both conclude that people tend to pay more for higher level of energy efficient buildings. Chau et al (2010) [20] apply discrete choice experiments to identify the factors affecting the preference for energy-efficient buildings in Hong Kong.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation